Medical Gas Plasma Jet Technology Targets Murine Melanoma in an Immunogenic Fashion. Issue 10 (30th March 2020) - Bekeschus, Sander; Clemen, Ramona; Nießner, Felix; Sagwal, Sanjeev Kumar; Freund, Eric; Schmidt, Anke
Abstract: Medical technologies from physics are imperative in the diagnosis and therapy of many types of diseases. In 2013, a novel cold physical plasma treatment concept was accredited for clinical therapy. This gas plasma jet technology generates large amounts of different reactive oxygen and nitrogen species (ROS). Using a melanoma model, gas plasma technology is tested as a novel anticancer agent. Plasma technology derived ROS diminish tumor growth in vitro and in vivo. Varying the feed gas mixture modifies the composition of ROS. Conditions rich in atomic oxygen correlate with killing activity and elevate intratumoral immune‐infiltrates of CD8 + cytotoxic T‐cells and dendritic cells. T‐cells from secondary lymphoid organs of these mice stimulated with B16 melanoma cells ex vivo show higher activation levels as well. This correlates with immunogenic cancer cell death and higher calreticulin and heat‐shock protein 90 expressions induced by gas plasma treatment in melanoma cells. To test the immunogenicity of gas plasma treated melanoma cells, 50% of mice vaccinated with these cells are protected from tumor growth compared to 1/6 and 5/6 mice negative control (mitomycin C) and positive control (mitoxantrone), respectively. Gas plasma jet technology is concluded to provide immunoprotection against malignant melanoma both in vitro and in vivo. Abstract : Cancer is among the leading causes of death worldwide, motivating the need for novel therapeutic concepts in oncology. In chorus, the immune system is a significant contributor to tumor control. Utilizing a novel medical gas plasma technology concept and melanoma as model tumor, reduction in tumor mass as well as antitumor immuno‐stimulation is demonstrated in a reactive oxygen species dependent fashion.